Determination of spatial factors in measuring urban sprawl in Kuantan using remote sensing and GIS - Hj. Mohd. Noor, Norzailawati; Nur Aulia, Rusni (Elsevier, 2013)
Abstract Characterizing urban sprawl by using spatial measures require a concise definition of what constitutes urban sprawling spatial patterns. This research attempts to study the measurement of defining sprawl by using spatial factors indexes such as highway strip, land use segregation and leapfrog development through remote sensing and GIS approach. The IKONOS pan-sharpened and SPOT-5 with 1 and 2.5 meters resolution were used and combined with GIS database to analyze the geospatial indicators using these indexes. The study area for this research is Kuantan city in order to examine the urban sprawl development of the city based on 2012 land use pattern. Kuantan city was selected due to the high growth rate of its population and the rapid establishment of new town area. To achieve better future urban development and infrastructure planning, it is crucial for the municipal authorities to know sprawl phenomenon happening in Kuantan, its types, distribution, factors, and the way the phenomenon is likely to move in the years to come. The finding shows that characterization of highway strip, land use segregation and leapfrog development spatial factors has resulted in identifying Kuantan as non-sprawl city. The result of using highway strip development spatial factors in measuring urban sprawl development show high gap between sprawl and non-sprawl percentages which indicates urban sprawl is not a thread. However, measuring sprawl based on land use segregation and leap frog development shows the gap of sprawl was lower compared to the highway strip development measures. This situation needs to ensure the sprawl issues can be managed efficiently by the responsible authorities. Finally, it is anticipated that this research will provide a new direction in urban sprawl studies and represent a robust analytic approach for characterizing urban development in the city scale at once as well as promoting a city via GIS & Remote Sensing technology and catalyst the human behaviour relationship. Keywords: Urban Sprawl Measurement,Spatial Factors, Geospatial Indices, Remote Sensing and GIS